Strategy for Improving the Quality of Public Services at the Buton Regency Population and Civil Registration Service - Nurdin (Papsel Journal of Humanities and Policy, 2024)
The main problems that are the focus of this research are: (1) What strategies to improve the quality of public services are carried out by the Population and Civil Registration Service of Buton Regency? (2) What factors influence the quality of public services at the Buton Regency Population and Civil Registration Service? The research location is the Population and Civil Registration Service of Buton Regency. This research uses a qualitative descriptive approach, the sampling technique uses Purposive Sampling with primary data from in-depth interviews supported by documentary data and field observations. The data analysis technique uses qualitative analysis, namely an interactive analysis model through data reduction, data presentation and drawing conclusions. From the research results, it was concluded that the strategy implemented by the Buton Regency Population and Civil Registration Service has generally worked well, although it has not been fully implemented, this has been felt by the community. The failure to implement this strategy optimally is caused by a lack of communication between authorities, because there are no local government regulations that clearly regulate communication patterns between authorities.